A Role for YouTube in Telerehabilitation - M. Hunter Manasco; Nicholas Barone; Amanda Brown (International Journal of Telerehabilitation)
YouTube is a free video sharing website that allows users to post and view videos. Although there are definite limitations in the applicability of this website to telerehabilitation, there are possible uses that should not be overlooked. Certain types of therapy, such as errorless learning therapy for certain language and cognitive deficits can be provided remotely via YouTube. In addition, negative emotional reactions to deficits are known to delay or halt recovery. The social networking capability YouTube provides enables individuals with health problems that may be unable to leave their houses an opportunity to gain valuable emotional support by meeting and communicating with others with similar problems. This article address the benefits and limitations of YouTube in the context of telerehabilitation and reports patient feedback on errorless learning therapy for aphasia delivered via videos posted on YouTube.